1982
DOI: 10.1104/pp.70.3.668
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Nitroxide Spin Labels with Chloroplasts

Abstract: Chloroplasts isolated from oats eliminated the electron spin resonance (ESR) signals from spin labels in white light and partially restored them in far-red light. Only the white lght-mediated reaction was blocked by 3-(3,4-dichlorophenyl)-1,1,-dimethylurea (DCMU). In contrast, oat (Avena sativa L. cv. Garry and Park) leaf mesophyli protoplasts oxidized the spin labels in both white and far-red light, with and without DCMU. Light had no obvious effect on spin label motion within chloroplast membranes. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…However, ascorbate caused no significant reduction of PC (5,10). The results with PC(5, 10) are consistent with those of Rousselet et al (21) who found that 1 h was required to completely reduce PC (10,3) in the outer leaflet of erythrocyte membranes, but that 4 h were required for comparable reduction of PC (7,6). PC(m,n) spin labels are probably more resistant to ascorbate reduction than are I(m,n) spin labels because PC(m,n) labels have greater stability in the membrane; I(m,n) spin labels may orient in bilayers such that their nitroxyl and carboxyl groups are at the membrane surface (9) facilitating interaction with ascorbate.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, ascorbate caused no significant reduction of PC (5,10). The results with PC(5, 10) are consistent with those of Rousselet et al (21) who found that 1 h was required to completely reduce PC (10,3) in the outer leaflet of erythrocyte membranes, but that 4 h were required for comparable reduction of PC (7,6). PC(m,n) spin labels are probably more resistant to ascorbate reduction than are I(m,n) spin labels because PC(m,n) labels have greater stability in the membrane; I(m,n) spin labels may orient in bilayers such that their nitroxyl and carboxyl groups are at the membrane surface (9) facilitating interaction with ascorbate.…”
Section: Discussionsupporting
confidence: 82%
“…Oxidation seems to take place within chloroplast membranes but only if the protoplasts are intact; isolated chloroplasts reduce spin label in the light (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation